THE RELATIONSHIP OF NURSES' CARING BEHAVIORS AND THE IMPLEMENTATION OF PATIENT SAFETY IN EMERGENCY DEPARTMENT (ED) - Ilkafah, Ilkafah; Indira Pramesty, Permata; Rahmadi Purwanto, Cucuk; Pangestu Mei Tyas, Anestasia; Susanto, Joko (Journal of Vocational Nursing, 2025)
Introduction: Patient safety remains a primary concern in healthcare, focusing on the prevention of medical errors and adverse side effects affecting patients. Despite numerous efforts to improve patient safety, incidents continue to occur, resulting in significant harm to patients. One critical factor in addressing this issue is the role of caring behaviors. Nurses' caring behaviors can serve as a strategy to enhance patient safety. This study aimed to investigate the relationship between nurses' caring behaviors and the implementation of patient safety protocols in the Emergency Department (ED) of Dr. Soegiri Lamongan Hospital. Methods: A correlational research design was employed using a cross-sectional approach. The study involved 28 nurses working in the Emergency Room. The instruments used included the CBI-24 (Caring Behavior Inventory) and a patient safety implementation questionnaire based on the International Patient Safety Goals (IPSG). Data were analyzed using univariate analysis (frequency distribution and percentage) and bivariate analysis (Coefficient of Contingency, with a p-value < 0.05). Results: The results showed that most nurses exhibited caring behaviors, with 18 respondents (64.3%) demonstrating these behaviors, and the majority had implemented patient safety protocols, with 21 respondents (75%) adhering to these measures. The coefficient of contingency test yielded a p-value of 0.023. Conclusions: A significant relationship was found between nurses' caring behaviors and the implementation of patient safety in the Emergency Department. This study highlights the critical role that nurses' caring behaviors play in enhancing patient safety. It is recommended that nurses continue to improve their caring behaviors and implement patient safety measures effectively. This approach will contribute to providing professional and cautious services, thereby improving the overall quality and safety of patient care.